ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARI'AH DENGAN PERBANKAN KONVENSIONAL - Diah Tri Susanti; Akhmad Sakhowi; Mahirun Mahirun (Fakultas Ekonomi Universitas Pekalongan, 2019)
This study aims to analyze the financial performance comparison between Islamic banking and conventional banking, using profitability ratios are represented by Return on Assets (ROA) as dependent variables and analyze the variables that affect the profitability of banks is Finance to Deposit Ratio (FDR), Ratio Operating costs with Revenues Operations (BOPO), Adiquasi Capital Ratio (CAR) and Reserve Elimination Receivables (PPAP).Methods using multiple linear regression analysis, chow test and independent sample t-test (test dlff], sample uses three Islamic banks and conventional, while the data used are secondary data are reported quarterly financial reports to Bank Indonesia as well as publicized the period June 2007 - June 2010.The results showed that in Islamic banking, CAR and PPAP no significant positive effect on ROA, LOR and no significant negative effect on ROA. BOPO significant negative effect on ROA. In conventional banking, LOR is not significant positive effect on ROA, CAR and PPAP no significant negative effect on ROA. BOPO significant negative effect on ROA. Chow test results states that there are significant differences in the influence of four independent variables on ROA in Islamic banking and conventional banking.Different test states that the ROA ratio, LOR and PPAP Islamic banking is better than conventional banking, and there are significant differences, for BOPO ratio is better than the conventional banking and Islamic banking there Is no significant difference,Keyword : Islamic Banking, Conventional Banking, ROA, LDR, BOPO, CAR, PPAP